Effect of different diets of full fat soybean (flake) on the organoleptic quality of broiler meat - DS Rasane; SS Kamble (Journal of Livestock Biodiversity, 2025)
A study was carried out on organoleptic quality of broiler meat when fish meal (FM) was replaced by different levels of full fat soybean (FFSB) in the ration. In terms of colour and appearance the score was 6.63, 6.85, 7.20 and 7.27 in T, T, T,and T,. The colour and appearance of meat scored highest in 15 per cent FFSB. It was observed that with increasing level of inclusion of FFSB increased the score for colour and appearance. Tenderness of meat was not affected significantly by different treatment diets. The average score for juiciness of meat was higher in 15 per cent FFSB (7.36) and lowest in FM diet (6.55) differed significantly (P < 0.05). The higher score for juiciness in 15 and 10 per cent FFSBdiets was due to the higher fat content of meat. The average score for meat flavour was highest in 15 per cent FFSB (7.31) and lowest in FM diet (6.60). The flavour of meat with FFSB diet was significantly superior (P < 0.05) than fish meal diet. The average score for acceptability of meat was maximum in 10 per cent FFSB (7.60) and minimum in FM diet (6.60). The acceptability of meat was significantly higher (P < 0.01) in FFSB diets as compared to FM diet